Optimal self-tuning decoupled sliding mode control for a class of nonlinear systems. (16th January 2020) - Mahmoodabadi, M.J.; Yazdi, S.M. Mortazavi; Talebipour, M.
A decoupled sliding mode controller (DSMC) is well-known as a simple way to achieve asymptotic stability of the nonlinear under-actuated systems. This method has many advanced features such as good performance and robustness against parameter variations. However, because of changing the system states, the controller with the constant parameters would not be optimum in any state of the system, and designing DSMC requires an adaptation for the controller parameters. Hence, in this paper, a robust self-tuning decoupled sliding mode controller (RSDSMC) is presented and optimised with five conflicting objective functions and twelve design variables using a multi-objective genetic algorithm. The proposed controller is applied to a highly nonlinear inverted pendulum and cart system via the computer simulation. The final results depict the appropriate performance of this new controller and demonstrate its superiority in comparison with those reported in literature.